(3TQM GdbUjOI GdMdhGfjI dCHi YHO Gddg eMeO Hf SYjO GdcGJHs - (3ZGRi Hf jRjOs; (3YQjH Hf SYjO GdcGJH GdbQWHjs ((3Mdje Hf eMeO Hf MfLQ Hf SYjO Hf ZajdI s)
(3ChdgG (B:s
(3hHYO ,aEfg LQi HHYV CfOjI GdBOGH YfO Pi GdMLG hGdCdHGH hGdaVd GddHGH PcQ bUjOI ddTjN GdCLd GdCaUdp CHi YHO Gddg eMeO Hf SYjO GdcGJH s
(3BNQgG (B:s
(3ge HGdfOi ai LGQMI hSe TQhG cd HGbi GdPcQ HGdYQV GdaGfi s
(3hGdbUjOI ai EaJNGQ GdbMWGfjI Ydi GdYOfGfjI hEXgGQ aVd GdjeGfjI Ydi GdfRGQjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs